2017
DOI: 10.1111/vsu.12670
|View full text |Cite
|
Sign up to set email alerts
|

Response to early repeat celiotomy in horses after a surgical treatment of jejunal strangulation

Abstract: Repeat celiotomy can eliminate signs of POR and/or POC, and the additional surgery does not appear to aggravate POR. Criteria for repeat celiotomy in this study could provide guidelines for managing POC and POR after surgery for jejunal strangulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Importantly, the above clinical signs may also be present in other conditions, particularly those associated with a mechanical obstruction to the aboral passage of SI ingesta and fluid. In a more recent study of 22 horses that underwent relaparotomy, 16 of 19 horses with precipitating clinical signs (POR and post-operative colic) had these clinical signs eliminated by relaparotomy; furthermore, the authors reported that relaparotomy did not appear to exacerbate the POR [27]. Clinical distinction between a functional and physical obstruction is challenging.…”
Section: Diagnosis Of Equine Poimechanical Versus Functionalmentioning
confidence: 99%
“…Importantly, the above clinical signs may also be present in other conditions, particularly those associated with a mechanical obstruction to the aboral passage of SI ingesta and fluid. In a more recent study of 22 horses that underwent relaparotomy, 16 of 19 horses with precipitating clinical signs (POR and post-operative colic) had these clinical signs eliminated by relaparotomy; furthermore, the authors reported that relaparotomy did not appear to exacerbate the POR [27]. Clinical distinction between a functional and physical obstruction is challenging.…”
Section: Diagnosis Of Equine Poimechanical Versus Functionalmentioning
confidence: 99%
“…Also, in the author's experience, anastomotic impactions develop within the first 12 h post‐operatively (Bauck et al . ), presumably because the only remaining solid material is moved from the stomach or proximal small intestine to the anastomosis in that timeframe. Early provision of energy is not the goal of an early refeeding programme, although refeeding can prevent hypertriglyceridaemia and eliminate the need for parenteral nutrition (Underwood et al .…”
Section: Post‐operative Feedingmentioning
confidence: 99%
“…Horses with incisional drainage were 17.8–62.5 times more likely to develop an incisional hernia than horses without incisional drainage 6,31 . Repeat laparotomy performed through the same incision is a risk factor for incisional infections as well as incisional hernias 2,78–80 . The incidence of incisional hernias was 8% in 300 horses that underwent 1 emergency celiotomy; hernia rate increased to 25% following a second surgery performed through the same incision 79 .…”
Section: Introductionmentioning
confidence: 99%